Optimization of Pyrocatechol and p-Cresol adsorption onto a composite of Chitosan and polyacrylamide incorporated with zeolitic imidazolate Framework-8 - Chou-Yi Hsu; Ebraheem Abdu Musad Saleh; M. M. Moharam; Mohammad Y. Alshahrani; Sandeep Singh; Aditya Kashyap; T. Krithiga; Parul Chaudhary; Nezamaddin Mengelizadeh; Davoud Balarak (Scientific Reports)
Abstract The objective of the current research was to adsorb pyrocatechol and p-cresol from a water-based solution using CS-PAA-ZIF-8. Response surface methodology (RSM) using central composite design (CCD) was utilized to examine and optimize the process variables. These variables included pH, concentrations of pyrocatechol and p-cresol, mass of the adsorbent, and contact time. Quadratic models with a coefficient of determination (R2) of 0.99 (p < 0.0001) were statistically compared. The findings indicated that the chosen models exhibit strong precision and a significant alignment between the projected and experimental data. The optimal removal conditions consisted of pH of 5, a concentration of 25 mg/L, a CS-PAA-ZIF-8 dosage of 0.8 g/L, and a contact time of 60 min. Under these circumstances, the removal efficiencies (Experimental) for pyrocatechol and p-cresol were 98.4% (%R Predicted: 99.1) and 96.1% (%R Predicted: 97.3), respectively. The adsorbent was found to be reusable up to 5 times in water and wastewater treatment processes, according to the assessment of its reusability. The kinetics of the evaluated process aligned well with the PSO, and the adsorption capacities of pyrocatechol and p-cresol on CS-PAA-ZIF-8, as deduced from the Langmuir model, were 180.1 and 171.5 mg/g at a temperature of 50 °C. Consequently, the optimized method can be broadly applied with high effectiveness for eliminating pyrocatechol and p-cresol from water and wastewater samples.